Remote Criminal Proceedings in EU Law from the Perspective of Strengthening the Rights of the Accused - Žukovaitė Inga (Baltic Journal of Law & Politics)
This article analyses remote proceedings as a new form of participation in the criminal process in the context of EU law, with particular reference to the question of whether remote participation could be considered (and established) as part of the defendant’s right to be present at their trial. The question of how technological developments may be used to strengthen the rights of the accused is also considered. The author explores the EU legal framework promoting the use of video conferencing tools as innovative technologies, while also considering the perspective that sees them as representing a practical risk to the observance of procedural rights. The requirement that a videoconference hearing must meet the standards established by the European Court of Human Rights is identified. Following this, the question of whether a videoconference hearing can become an instrument that balances the protection of the rights of the accused with progressive e-justice digitalisation processes when adequately regulated in EU law is addressed. The article concludes with proposals relating to the measures that need to be implemented to effectively protect the rights of the accused, along with steps that should be taken to amend the relevant legislation.